The Upper Room: A University-Archdiocesan Partnership to Develop Leaders for Catholic Schools - Cook, Timothy J.; Durow, W. Patrick (Catholic Education: A Journal of Inquiry and Practice, 2008)
In Renewing Our Commitment to Catholic Elementary and Secondary Schools in the Third Millennium, the United States Conference of Catholic Bishops (USCCB; 2005) calls on Catholic colleges and universities to work with diocesan educational leaders to prepare leaders for Catholic schools. In response, the Creighton University Education Department and the Archdiocese of Omaha’s Catholic Schools Office formed a task force that held a series of meetings in the “Upper Room” on Creighton’s campus to create a framework for leadership in Catholic schools and develop a preparation program that fulfills the framework. This article describes the task force process, framework development, and the Catholic School Leadership graduate certificate that resulted. The article concludes with observations related to the Omaha experience and thoughts about what comes next.